"We aren't after a House Negro to prove our love for Black People": the complicated relationship between George S. Schuyler and the John Birch society. Issue 2 (2nd July 2020) - Russler, Brett
ABSTRACT: Scholars have taken great interest in black conservatism, but most focus on the ideology's contours during the post-civil rights era. Few closely interrogate the relationship between black conservatives and white conservative groups, particularly during the height of the civil rights movement. This article takes a close look at the partnership between black conservative George S. Schuyler and the rabidly anticommunist John Birch Society during the 1960s and 1970s. Black conservatives like Schuyler have often been dismissed as race traitors. However, Schuyler often used his conservative platforms to challenge racism, even among his right-wing audience. This reveals a complicated relationship and an unexpected black conservative politics that encompassed elements of the black freedom struggle once thought reserved for black liberals and nationalists.